International survey on periextubation practices in extremely preterm infants. Issue 5 (10th June 2015) - Al-Mandari, H; Shalish, W; Dempsey, E; Keszler, M; Davis, P G; Sant'Anna, G
Abstract : Objective: To determine periextubation practices in extremely preterm infants (<28 weeks gestation). Design: A survey consisting of 13 questions related to weaning from mechanical ventilation, assessment of extubation readiness and postextubation respiratory support was developed and sent to clinical directors of level III NICUs in Australia, Canada, Ireland, New Zealand and USA. A descriptive analysis of the results was performed. Results: 112/162 (69%) units responded; 36% reported having a guideline (31%) or written protocol (5%) for ventilator weaning. Extubation readiness was assessed based on ventilatory settings (98%), blood gases (92%) and the presence of clinical stability (86%). Only 54% ensured that infants received caffeine ≤24 h prior to extubation. 16% of units systematically extubated infants on the premise that they passed a Spontaneous Breathing Test with a duration ranging from 3 min (25%) to more than 10 min (35%). Nasal continuous positive airway pressure was the most common type of respiratory support used (84%) followed by nasal intermittent positive pressure ventilation (55%) and high-flow nasal cannula (33%). Reintubation was mainly based on clinical judgement of the responsible physician (88%). There was a lack of consensus on the time frame for definition of extubation failure (EF), the majority proposing a period between 24 and 72 h; 43% believed that EF is an independent risk factor for increased mortality and morbidity. Conclusions: Periextubation practices vary considerably; decisions are frequently physician dependent and not evidence based. The definition of EF is variable and well-defined criteria for reintubation are rarely used. High-quality trials are required to inform guidelines and standardise periextubation practices.